Antioxidant activity and electrochemical elucidation of the enigmatic redox behavior of curcumin and its structurally modified analogues. (1st January 2015) - Jha, Niki S.; Mishra, Satyendra; Jha, Shailendra K.; Surolia, Avadhesha
Graphical abstract: Highlights: Structural analogues of curcumin have been synthesized. Confirmation of redox behaviour emanates from H- shift from central methylene group in curcumin. Mechanism of curcumin oxidation has been proposed. Correlation between redox behavior and antioxidant activity has been established. Abstract: Here, we report studies on the antioxidant activity and redox behavior of curcumin and its structurally modified synthetic analogues. We have synthesized a number of analogues of curcumin which abrogate its keto-enol tautomerism or substitute the methylene group at the centre of its heptadione moiety implicated in the hydride transfer and studied their redox property. From cyclic voltammetric studies, it is demonstrated that H- atom transfer from CH2 group at the center of the heptadione link also plays an important role in the antioxidant properties of curcumin along with that of its phenolic –OH group. In addition, we also show that the conversion of 1, 3- dicarbonyl moiety of curcumin to an isosteric heterocycle as in pyrazole curcumin, which decreases its rotational freedom, leads to an improvement of its redox properties as well as its antioxidant activity.